2009
DOI: 10.1210/me.2008-0277
|View full text |Cite
|
Sign up to set email alerts
|

The Orphan Nuclear Receptor RORα Restrains Adipocyte Differentiation through a Reduction of C/EBPβ Activity and Perilipin Gene Expression

Abstract: The nuclear receptor-type transcription factor retinoic acid receptor-related orphan receptor alpha (RORalpha) is a multifunctional molecule involved in tissue development and cellular function, such as inflammation, metabolism, and differentiation; however, the role of RORalpha during adipocyte differentiation has not yet been fully understood. Here we show that RORalpha inhibits the transcriptional activity of CCAAT/enhancer-binding protein beta (C/EBPbeta) without affecting its expression, thereby blocking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 60 publications
3
50
1
Order By: Relevance
“…First, consistent with the earlier study [72], it was observed that Ror˛ was induced during the differentiation of 3T3-L1 mouse adipocytes, but unusually, the time course of induction was delayed in comparison with other early markers of adipogenesis [77,78]. Using either siRNA knockdown of Ror˛ in 3T3-L1 cells [78] or ex vivo mouse embryonic fibroblasts (MEF) derived from sg/sg mice [77], both groups demonstrated improved adipogenesis upon differentiation.…”
Section: Adipose Tissuesupporting
confidence: 86%
“…First, consistent with the earlier study [72], it was observed that Ror˛ was induced during the differentiation of 3T3-L1 mouse adipocytes, but unusually, the time course of induction was delayed in comparison with other early markers of adipogenesis [77,78]. Using either siRNA knockdown of Ror˛ in 3T3-L1 cells [78] or ex vivo mouse embryonic fibroblasts (MEF) derived from sg/sg mice [77], both groups demonstrated improved adipogenesis upon differentiation.…”
Section: Adipose Tissuesupporting
confidence: 86%
“…Furthermore, sg/sg mice display reduced adiposity, increased metabolic rate, improved insulin sensitivity, resistance to diet-induced obesity, and hepatic steatosis (17,18). However, studies utilizing either 3T3-L1 cells or sg/sg MEF cells have indicated a contrary role whereby attenuation of Ror␣ enhanced adipogenesis (11,30). Therefore, we investigated overall body composition and adi-posity [by dual-energy X-ray absorptiometry (DEXA) and MRI] and then analyzed adipose tissue samples [by quantative PCR (qPCR) and Western blotting], comparing sg/sg mice with their wild-type (WT) counterparts.…”
mentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor gamma (PPARγ) and CCAAT/enhancer binding proteins (C/EBPs) are master transcription factors involved in adipogenesis and obesity development (6)(7)(8). Moreover, p300, a histone acetyltransferase (9), has been shown to promote adipogenesis through regulation of PPARγ and C/EBPβ expression (10,11). Despite a wealth of knowledge at the transcription level (5), intracellular signaling cascades underlying adipogenesis are not fully understood, with fragmented or controversial data in the literature (12)(13)(14).…”
mentioning
confidence: 99%